Personal Branding Finalis Pemilihan Putra-Putri Perdamaian Provinsi Bali 2021 Pada Media Sosial Instagram (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2023)
Someone in maturity period usually build identity. The process of character building, which is commonly known as personal branding, can be accomplished through the use of Instagram, a social media platform that is widely popular among online users aged 18-29, representing 59% of its user base. Peace Ambassador is one of talent contest which is open recruitment from promoted Instagram and invited several agencies for young generation to join as part of peae ambassador. Based on research, that image, reputation and principles of peace showing in front of stage by contestant of Peace Ambassador so nicely in front of Instagram screen. This is done as rules from recruitment and it porpuse sharing on peace message via Instagram. While in the back stage contestant of Peace Ambassador is private and closed from audiens. There is thoughtful preparation for supported appearance in front Instagram stage and another side for formed character Peace Ambassador contestant in real life. The expected impact that Peace Ambassador contestant hope from reputation building on Instagram is to get attention when act as agent of peace message. The theoretical framework utilized in this research is the Dramaturgical Theory, which was introduced by Erving Goffman. Based on research it is suggested that in the future can used social media wisely and then peaceful and harmonious interactions are realized so as to provide positive affirmations to the community. Keywords: Character, Peace, Front region, Back region and Peace Ambassador contestant.